Hubungan Obesitas Dengan Diabetes Melitus Tipe 2: Tinjauan Literatur Tentang Mekanisme Patofisiologi Dan Implikasi Klinis - Kadek Wulan Indra Mahiswari; IP Adi Wibowo; Putu Adi Suputra; I Gede Yuda Mahendra; Kadek Febi Rustiana Dewi (LPPM ITEKES Mahardika, 2025)
The prevalence of adult obesity reached 23.4% in 2023 and is predicted to increase annually. Obesity is often considered a major risk factor for the development of the metabolic disease type 2 diabetes mellitus (T2DM), which can affect glucose metabolism and insulin sensitivity. This literature review aims to analyze the relationship between obesity and T2DM. The method used was a qualitative literature review through PubMed and Google Scholar. The initial search yielded 44 articles, and after selection, 19 articles were identified for duplication and relevance. These articles were then re-screened based on inclusion and exclusion criteria, leaving only eight eligible articles. The selected literature met the inclusion and exclusion criteria and was published within the last 10 years. The analysis showed that increased body mass index (BMI), visceral fat accumulation, and imbalanced fat distribution significantly contribute to an increased risk of T2DM. Obesity management strategies through lifestyle modification, pharmacological therapy, and surgical intervention have been shown to be effective in reducing the risk of T2DM and improving patient glycemic control. These findings emphasize the importance of obesity prevention and management as an integral part of efforts to reduce the incidence of T2DM.